FISHERIES POTENTIALS OF CHALLAWA DAM, KANO STATE, NIGERIA - Suleiman, Nazeef; Yola, Idris Ado; Ahmed, Ibrahim Muhammad (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Morpho-metrics and total nutrient input of Challawa dam, Kano State (Nigeria) were applied to estimate the potential fish yield using morpho-edaphic index (MEI). Physico-chemical parameters of the reservoir were sampled monthly from three stations for the period of six months (March to August, 2017) using standard methods. Potential fish yield estimates of the reservoir was determined using the values of the Physico-chemical characteristics of the reservoir with the relationship Y=23.281 MEI 0.447, where Y is the potential fish yield in kg/ha, MEI is Morphoedaphic index (given in μS/cm) which was obtained by dividing mean conductivity of the reservoir by mean depth. The values of the mean conductivity and mean depth were 92μS/cm and 3.8m respectfully, with the potential estimate being 96.84kg/ha. The relative yield index (RYI) which is the ratio of estimated yield with angler harvest, was determined using the relationship RYI= Yobs/Yest × 0.75, where Yest is estimated potential yield in Kg/ha and Yobs is anglers harvest in Kg. The estimated yield (Yest) value obtained and anglers harvest were 96.84kg/ha and 35.7kg respectfully, which implied that the relative yield index was 0.27and 27.6%. This result showed that, the reservoir‟s exploitation level was moderate. Therefore effective management system, implementation of good fishing regulations and practices should be implemented.